The Role of Non-Metal Doping in TiO2 Photocatalysis - Yalcin, Yelda; Kilic, Murat; Cinar, Zekiye (WALTER DE GRUYTER GMBH, 2010)
The visible light activity of TiO2 (Degussa P25) particles was improved by non-metal-doping. In order to characterize and describe the effect of anion-doping on the electronic and structural properties of TiO2, a combination of experimental structural methods and DFT calculations were used. A series of N, C and S-doped photocatalysts with different dopant contents were prepared by an incipient wet impregnation method, followed by calcination at three different temperatures for 1h, 3h and 5h. An obvious extension of the absorption to the visible region was observed by UV-DRS. The doped photocatalysts were characterized by XRD, XPS and Raman spectroscopy. The morphological structure of the photocatalysts was examined by HR-TEM. In the computational part of the study, a neutral, stoichiometric cluster Ti9O27H18 cut from the anatase bulk structure and new models for the substitutional and interstitial anionic and cationic-doped TiO2 were developed. The DFT calculations were carried out by the hybrid B3LYP functional, by using double-zeta, LanL2DZ basis set. The experimental results combined with DFT calculations, indicate that substitutional N, interstitial cationic C, and substitutional cationic S-doping of TiO2 occur in the as-prepared samples. The band-gap reduction arises from the contribution of N 2p, C 2p and S 3p orbitals to the O 2p and Ti 3d states in the VB of TiO2, as well as the presence of C and S induced mid-gap states in the band-gap. The photocatalytic activity of the doped TiO2 photocatalysts was also determined by investigating the kinetics of the photocatalytic degradation of 4-nitrophenol under UV-A and solar light irradiation.
Keywords: TiO2; N-doped; C-doped; S-doped; DFT Calculations; Heterogeneous Photocatalysis; 4-Nitrophenol; S-DOPED TIO2; PHOTOELECTROCHEMICAL PROPERTIES; DEGRADATION; SUSPENSIONS; WATER; FILM; Chemistry